2023
DOI: 10.1021/acs.jcim.2c01184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the QM Size, Basis Set, and Polarization on QM/MM Interaction Energy Decomposition Analysis

Abstract: Herein, an Energy Decomposition Analysis (EDA) scheme extended to the framework of QM/MM calculations in the context of electrostatic embeddings (QM/MM-EDA) including atomic charges and dipoles is applied to assess the effect of the QM region size on the convergence of the different interaction energy components, namely, electrostatic, Pauli, and polarization, for cationic, anionic, and neutral systems interacting with a strong polar environment (water). Significant improvements are found when the bulk solvent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 80 publications
1
13
0
2
Order By: Relevance
“…20 Similarly, the size of the QM region and its contribution to the convergence of EDA terms in QM/MM were also studied with respect to the solvation of small organic ions. 21 Here, we apply the GKS-EDA(QM/MM) study with different MM force fields for a system that includes a hydronium ion in water. Figure 5 shows the computational results of GKS-EDA(QM/MM) for H 3 O + ••• water interactions with various force fields and MM programs.…”
Section: Gks-eda(qm/mm) Results With Different Qm/ MM Programs and Mm...mentioning
confidence: 99%
“…20 Similarly, the size of the QM region and its contribution to the convergence of EDA terms in QM/MM were also studied with respect to the solvation of small organic ions. 21 Here, we apply the GKS-EDA(QM/MM) study with different MM force fields for a system that includes a hydronium ion in water. Figure 5 shows the computational results of GKS-EDA(QM/MM) for H 3 O + ••• water interactions with various force fields and MM programs.…”
Section: Gks-eda(qm/mm) Results With Different Qm/ MM Programs and Mm...mentioning
confidence: 99%
“…Solvent effects were introduced with the ALPB model, 78 suitable for XTB. Although the inclusion of water molecules in the QM region could lead to PCCP Paper more reliable results, a very large number of water molecules could be needed to obtain converged results, 79 making the calculations computationally unfeasible. In addition, previous computational work has shown that the use of implicit solvation provides accurate oxidation potentials for the nucleobases.…”
Section: Methods and Computational Detailsmentioning
confidence: 99%
“…10). 218 Hence, IQA and other EDAs 220 could help in the diagnosis of QM/MM methodological problems and in the evaluation of possible solutions.…”
Section: Energy Decompositionsmentioning
confidence: 99%